1983
DOI: 10.1051/forest:19830306
|View full text |Cite
|
Sign up to set email alerts
|

Influence d'une réhydratation préalable sur la germination in vitro du pollen de douglas (Pseudotsuga menziesii) après conservation

Abstract: Centre de Recherrhc•s d 'Orléa l 1s, Ar d ol1, F 45160 Olivet Résumé Après avoir précisé les conditions de germination in vitro du pollen de douglas (I!.1!PLI(IOtS'Lfgci I77PI71 W ' ,S'(f), nous avons défini les modalités d'utilisation d'un pollen déshydraté avant conservation. Pour la mise en route du processus de germination, une phase préalable d'hydratation ménagée s'est avérée indispensable. Cette hydratation s'effectue bien à 26 "C pendant 16 h., en atmosphère saturée d'eau. Elle permet il certains lots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Webber and Bonnet-Masimbert [24] showed that, while respiration was not affected by a preconditioning of pollen in 100 % RH, significantly less leaching occurred in rehydrated pollen than in dry pollen. Furthermore, a slow rehydration of the pollen improved pollen grain elongation [24] and promoted ultrastructural changes [6]. In our study, rehydration substantially improved both pollen grain survival and development, independently of media composition.…”
Section: Culture Mediasupporting
confidence: 58%
See 1 more Smart Citation
“…Webber and Bonnet-Masimbert [24] showed that, while respiration was not affected by a preconditioning of pollen in 100 % RH, significantly less leaching occurred in rehydrated pollen than in dry pollen. Furthermore, a slow rehydration of the pollen improved pollen grain elongation [24] and promoted ultrastructural changes [6]. In our study, rehydration substantially improved both pollen grain survival and development, independently of media composition.…”
Section: Culture Mediasupporting
confidence: 58%
“…To protect the plasma membrane of dry pollen against water stress damage occurring upon rapid rehydration [7], the pollen grains can be rehydrated in 100 % relative humidity (RH) prior to being put onto media. Charpentier and BonnetMasimbert [6] have shown that such a treatment substantially improved pollen performance during the first step of germination, that is elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, pollen hydration is essential as the first step toward germination (Heslop-Harrison 1987). Pollen prehydration is necessary before in vitro germination occurs in Douglas-fir (Charpentier and Bonnet-Masimbert 1983) or loblolly pine (Pinus taeda L.) (Jett and Frampton 1990). In Douglas-fir, pollen prehydration improves conductivity measurements (lowers response), but it has little effect on respiration tests (Webber and Bonnet-Masimbert 1993).…”
Section: Pollen Testingmentioning
confidence: 99%
“…In Douglas-fir, pollen prehydration improves conductivity measurements (lowers response), but it has little effect on respiration tests (Webber and Bonnet-Masimbert 1993). Actual assay responses to prehydration effects vary with pollen water content (Charpentier andBonnet-Masimbert 1983, Jett andFrampton 1990) and are probably species specific.…”
Section: Pollen Testingmentioning
confidence: 99%
“…Failing to do so led to instant fatal damage to pollen put on culture media. Consequently, pollen was rehydrated in sterile conditions following the method of Charpentier and Bonnet-Masimbert (1983). Dry pollen was put into aluminum boats in an airtight plastic container lined with wet sterile filter paper.…”
Section: Methodsmentioning
confidence: 99%